ANALYSIS OF INSTRUMENTS FOR ASSESSING THE MATHEMATICAL CRITICAL THINKING ABILITY ON THE PYTHAGOREAN THEOREM MATERIAL - Afdella Zuniawati; Desta Nadia Putri; Anis; Shindi Purwaningtias; Sri Astuti Anggra Niwi Ningsih; Agung Putra Wijaya; Desrina Hardianti (Universitas Muhammadiyah Lampung, 2026)
Critical thinking skills are important to develop in students. This study was conducted to evaluate the quality of a test instrument in measuring the critical thinking skills of junior high school students on the Pythagorean Theorem material. The analysis was carried out through testing the validity, reliability, discriminating power, and difficulty level of the questions with the support of Microsoft Excel. The method used was descriptive quantitative with Grade VIII students selected through purposive sampling as research participants. The results of the study showed that the test instrument was 100% valid, had a reliability of 0.668 (moderate category), the discriminating power indicated questions 1 and 3 were in the fair category while question 2 was in the good category, and all questions had an easy level of difficulty.